2013
DOI: 10.1371/journal.pcbi.1003246
|View full text |Cite
|
Sign up to set email alerts
|

dPeak: High Resolution Identification of Transcription Factor Binding Sites from PET and SET ChIP-Seq Data

Abstract: Chromatin immunoprecipitation followed by high throughput sequencing (ChIP-Seq) has been successfully used for genome-wide profiling of transcription factor binding sites, histone modifications, and nucleosome occupancy in many model organisms and humans. Because the compact genomes of prokaryotes harbor many binding sites separated by only few base pairs, applications of ChIP-Seq in this domain have not reached their full potential. Applications in prokaryotic genomes are further hampered by the fact that wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Paired-end sequencing in ChIP-seq produces data in which both ends of every fragment are known and no inference of fragment size is necessary. dPeak 101 resolves complex paired-end ChIP-seq peak regions into multiple loci with a higher accuracy than single end analyses. The model used in dPeak takes non-specific binding into account and allows shift distributions to be non-uniform across all binding sites.…”
Section: Analytical Techniques For Bias Correctionmentioning
confidence: 99%
“…Paired-end sequencing in ChIP-seq produces data in which both ends of every fragment are known and no inference of fragment size is necessary. dPeak 101 resolves complex paired-end ChIP-seq peak regions into multiple loci with a higher accuracy than single end analyses. The model used in dPeak takes non-specific binding into account and allows shift distributions to be non-uniform across all binding sites.…”
Section: Analytical Techniques For Bias Correctionmentioning
confidence: 99%
“…Some bacterial TFs bind to multiple, closely spaced locations within a promoter region (less than 100 bp separation) [46]. The ability to distinguish between these sites yields greater mechanistic insight into the transcriptional control mediated by the TF of interest.…”
Section: : Identifying Areas Of Enrichment In Chip-seq Experimentsmentioning
confidence: 99%
“…However, most standard peak finding algorithms are unable to resolve closely spaced binding sites, instead misidentifying these regions as a single binding site with the wrong genomic coordinates. To test for closely spaced binding sites, peak deconvolution algorithms such as CSDeconv [20,47], GEM [48], PICS [49] or dPeak [46] can be used. We found that dPeak was able to identify regions containing multiple TF binding sites, most of which were missed with standard peak finding algorithms [46].…”
Section: : Identifying Areas Of Enrichment In Chip-seq Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of csdeconv in data sets with a large number of enriched regions has not been practical due to its high computational cost (Wilbanks and Facciotti 2010). Other methods have also been proposed to identify multiple binding sites inside the same region (Guo et al 2010(Guo et al , 2012Zhang et al 2011;Chung et al 2013).…”
mentioning
confidence: 99%